2019
DOI: 10.1002/pen.25239
|View full text |Cite
|
Sign up to set email alerts
|

Wear of Biopolymers under Reciprocating Sliding Conditions against Different Counterfaces

Abstract: The objective of this study was to investigate the wear resistance of ultrahigh‐molecular weight polyethylene (UHMWPE) and crosslinked polyethylene (XLPE) against different counterfaces. Friction and wear studies were evaluated under dry reciprocating sliding conditions at room temperature. Ti6Al4V discs finished in polished, lapped, and ground conditions were reciprocated against polymer cylinders. In addition, abrasive wear studies were conducted using different abrasive grit sizes. The friction and wear pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…The wear and friction studies were performed with a reciprocating sliding motion tribometer, which is described in detail elsewhere. 16,17 Figure 1(a) and (b) shows the details of the tribometer and a typical test configuration used in this study. The Ti6Al4V disc was reciprocated against a polyethylene pin in non-conformal contact under dry reciprocating sliding conditions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The wear and friction studies were performed with a reciprocating sliding motion tribometer, which is described in detail elsewhere. 16,17 Figure 1(a) and (b) shows the details of the tribometer and a typical test configuration used in this study. The Ti6Al4V disc was reciprocated against a polyethylene pin in non-conformal contact under dry reciprocating sliding conditions.…”
Section: Methodsmentioning
confidence: 99%
“…The friction energy ( F E ) dissipated during one oscillating cycle with a stroke 2Δ x corresponded to the area within the friction loop hysteresis, as described in detail elsewhere. 16,17 The mean coefficient of friction (COF) ( f av ) represents the average value calculated from the data of the second half of the experiment. The test durations and tribological conditions are reported in Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…According to previous studies, highly cross-linked polyethylene (HXLPE) obtained by irradiation crosslinking of UHMWPE can significantly improve its wear resistance. 6,7 The increase in cross-linking can reduce the large strain plastic deformation and orientation capacity of UHMWPE, which enhances its wear rate. Ionizing irradiation, including γ ray and electron beam (E-beam) irradiation, leads to the generation of free radicals through the cleavage of C-C and C-H bonds within amorphous and crystalline phases in UHMWPE materials.…”
Section: Introductionmentioning
confidence: 99%
“…According to previous studies, highly cross‐linked polyethylene (HXLPE) obtained by irradiation cross‐linking of UHMWPE can significantly improve its wear resistance 6,7 . The increase in cross‐linking can reduce the large strain plastic deformation and orientation capacity of UHMWPE, which enhances its wear rate.…”
Section: Introductionmentioning
confidence: 99%
“…[ 4 ] Some studies have shown that polyether ether ketone (PEEK) has much higher wear resistance than UHMWPE. [ 5‐7 ] Thus, PEEK as an alternative material has become a new focus. PEEK is a biopolymer material with excellent biocompatibility, mechanical properties, and wear resistance, which has been successfully applied in spine repair surgery, and also shows a great potential in TJA treatment.…”
Section: Introductionmentioning
confidence: 99%